(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
A 26-year-old man was admitted complaining of two days of abrupt, jerky limb movements, a three-to-four-minute period of unconsciousness, tongue biting, and mouth foam. Despite not receiving regular antiepileptic medication, the patient had experienced a seizure episode a year prior. Upon inspection, the patient had minor cyanosis during convulsions and was sleepy but arousable. Hyponatremia (Na⁺ 118 mmol/L) and mild metabolic acidosis on ABG tests were found in laboratory examinations, indicating electrolyte imbalance-induced seizures. The generalized tonic-clonic epilepsy caused by severe hyponatremia was confirmed by the generalized spike and wave pattern on the EEG.